The Effect of Digital Business Model Innovation and Organizational Agility on the Performance of Insurance and Pension Fund Companies in Indonesia - Feb Sumandar; Rano Kartono Rahim; Mohamamd Hamsal; Asnan Furinto (Greenation International Journal of Tourism and Management, 2023)
Indonesia's financial asset structure is still heavily dominated by the banking sector, while the asset of non-bank financial industry are still very limited. Meanwhile, The Non-Bank Financial Industry Sector, particularly the insurance and pension fund sectors, plays an important role in supporting national development and as a source of domestic financing to support economic activity. To achieve sustainable performance, previous researches had revealed the influence of business model innovation and organizational agility. Based on this background, this study aims to examine whether business model innovation and organizational agility affect the performance of funding sustainability in the insurance and pension fund industry in Indonesia. This research was conducted a quantitative research approach. Observations using the time horizon are cross-sectional/one-shot in 2023. The unit of analysis is the social insurance and pension fund industry in Indonesia. The unit of observation is the management of social insurance and pension fund industry companies in Indonesia. The observation unit is the management of the companies. To analyze data, this study used the Partial Least Square (PLS) approach. The results of hypothesis testing show that digital business model innovation and organizational agility significantly affect the performance of funding sustainability in the insurance and pension fund industry in Indonesia. The digital business model innovation has a more significant role than organizational agility. Based on these findings, this study proposes a managerial implication for the management of the insurance and pension fund industry to enhance the digital business model innovation, which is supported by the improvement of organizational agility to enhance the company performance.